Artificial Intelligence and Cybersecurity Governance: Comparative Insights into National Defense Strategies - Widaningsih; Abdurrahman, Sholahuddin Shoum; Busairi, Hasan (Indonesian Scientific Publication, 2025)
Artificial intelligence (AI) is reshaping national cybersecurity strategies worldwide, offering both innovative defense mechanisms and complex new threats. This study examines how AI influences cybersecurity frameworks across the United States, United Kingdom, Singapore, Sub-Saharan Africa, and the European Union. The objective is to assess AI’s dual role as a tool for cyber defense and offense, and its broader implications for global digital stability. Using a comparative analytical framework, the research integrates qualitative data from national policy documents, institutional reports, and secondary literature. Key indicators include national AI strategies, public–private collaboration models, secure-by-design principles, and resilience metrics. Cross-case comparisons reveal structural gaps and highlight effective practices. Findings indicate a growing divide between advanced and developing regions. Technologically advanced economies have incorporated AI into predictive threat modeling and automated defense systems, while emerging regions face infrastructure constraints and fragmented regulations. The study also notes the escalating economic impact of AI-driven cybercrime, expected to exceed 10 trillion globally by 2025. Promising defense technologies such as immutable backups, predictive analytics, and AI-based Managed Detection and Response (MDR) are identified as critical components of modern cybersecurity systems. In conclusion, the integration of AI into cybersecurity demands balanced policies that foster innovation while ensuring ethical governance, global interoperability, and equitable capacity building. The study advocates harmonized regulatory standards, stronger public–private partnerships, and inclusive governance to enhance global cybersecurity resilience in the AI era.